The influence of the leadership of the principal and school committee on teacher performance - Rita Fajar Hidayati; Yasir Arafat; Alhadi Yan Putra (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to determine the effect of the leadership of the school principal and school committee on the performance of the teachers of the State Junior High Schools in Muaradua District, by using quantitative methods with this type of correlational research. The research population consisted of 107 teachers at the State Junior High School in Muaradua District. The research sample was 48 people. The sampling technique used purposive sampling technique, namely sampling by determining certain criteria. Data were analyzed using correlation analysis techniques and multiple regression. The results showed that: (1) The leadership of the principal has a positive and significant effect on the performance of the teachers of the State Junior High Schools in Muaradua District; (2) The school committee has a positive and significant effect on the performance of the teachers of State Junior High Schools in Muaradua District; and (3) The leadership of the principal and the school committee jointly have a positive and significant effect on the performance of the teachers of the State Junior High Schools in Muaradua District.